2012
DOI: 10.1161/circgenetics.111.961292
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chromosome 9p21 Variants and the Ankle-Brachial Index Identified by a Meta-Analysis of 21 Genome-Wide Association Studies

Abstract: Background Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. Methods and Results Continuous ABI and PAD (ABI≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ~2.5 million SNPs in HapMap. Linear and logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 59 publications
3
88
0
Order By: Relevance
“…96 One genomewide significant association on chromosome 9p21, rs10757269, was identified for ABI. Two candidate genes for PAD and 1 single nucleotide polymorphism for coronary artery disease were associated with ABI, DAB21P (rs13290547), CYBA (rs3794624), and rs1122608 (LDLR).…”
mentioning
confidence: 99%
“…96 One genomewide significant association on chromosome 9p21, rs10757269, was identified for ABI. Two candidate genes for PAD and 1 single nucleotide polymorphism for coronary artery disease were associated with ABI, DAB21P (rs13290547), CYBA (rs3794624), and rs1122608 (LDLR).…”
mentioning
confidence: 99%
“…In this study, we investigated the hypothesis that the 9p21 locus, which is the most replicated genetic marker for diseases such as CAD, peripheral artery disease, AAA, stroke, and intracranial aneurysms [4,5,6,7,8,9,10], is also associated with sporadic BAVMs. To test this hypothesis, we studied the distribution of two prototypical SNPs of chromosome 9p21 in two cohorts of BAVM cases and controls from Rome and Turin, Italy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that the 9p21 locus contains single nucleotide polymorphisms (SNPs) associated with myocardial infarction, coronary artery disease (CAD), peripheral artery disease, abdominal aortic aneurysms (AAA), intracranial aneurysms, and stroke [4,5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…25,26 Martinelli et al 25 suggest that the effect they observed is due to the lipid effects of the variants. 25,26 The effect of common CAD-associated genetic variants on general population samples has also yielded conflicting results. In a study among B3000 cases and 3000 controls, a gene score comprising nine SNPs was associated with CAD risk.…”
Section: Discussionmentioning
confidence: 98%